116k views
1 vote
5. Find at least the first 4 nonzero terms of the solution to (2 + 4x-2x^2)y"-12(z-1)y'-12y = 0, y(1) = 0, y'(1) =-1.

User Ade Crown
by
5.8k points

1 Answer

4 votes

We're set up to find a series solution to the ODE centered around
x=1. Let's first replace
z=x-1, so that


y(x)=y(z+1)\implies y'(x)=y'(z+1)\implies y''(x)=y''(z+1)

and we'll look for a series solution centered at
z=0. We have


y=\displaystyle\sum_(n\ge0)a_nz^n


\implies y'=\displaystyle\sum_(n\ge0)(n+1)a_(n+1)z^n


\implies y''=\displaystyle\sum_(n\ge0)(n+2)(n+1)a_(n+2)z^n

The ODE is then


(2+4x-2x^2)y''-12(x-1)y'-12y=\left(4-2(x-1)^2\right)y''-12(x-1)y'-12y=0

which in terms of
z is


\left(4-2z^2\right)y''-12zy'-12y=0

Substituting the series above into the ODE gives


\displaystyle4\sum_(n\ge0)(n+2)(n+1)a_(n+2)z^n-2\sum_(n\ge0)(n+2)(n+1)a_(n+2)z^(n+2)-12\sum_(n\ge0)(n+1)a_(n+1)z^(n+1)-12\sum_(n\ge0)a_nz^n=0


\displaystyle4\sum_(n\ge0)(n+2)(n+1)a_(n+2)z^n-2\sum_(n\ge2)n(n-1)a_nz^n-12\sum_(n\ge1)na_nz^n-12\sum_(n\ge0)a_nz^n=0


\displaystyle\left(8a_2+24a_3z+4\sum_(n\ge2)(n+2)(n+1)a_(n+2)z^n\right)-2\sum_(n\ge2)n(n-1)a_nz^n-12\left(a_1z+\sum_(n\ge2)na_nz^n\right)-12\left(a_0+a_1z+\sum_(n\ge2)a_nz^n\right)=0


\displaystyle(8a_2-12a_0)+(24a_3-24a_1)z+\sum_(n\ge2)\bigg[(4n^2+3n+2)a_(n+2)-(2n^2+10n+2)a_n\bigg]z^n=0

so that the coefficients follow the recurrence,


\begin{cases}a_0=y(0)=0\\\\a_1=y'(0)=-1\\\\a_n=(2(n-2)^2+10(n-2)+2)/(4(n-2)^2+3(n-2)+2)a_(n-2)=(2n^2+2n-10)/(4n^2-13n+12)a_(n-2)&\text{for }n\ge2\end{cases}

Thanks to the dependency between every other coefficient, we have
a_n=0 for all even-valued
n. Meanwhile,


a_1=-1


a_3=-\frac{14}9


a_5=-(700)/(423)


a_7=-(23,800)/(16,497)

so that


y(z)\approx-z-\frac{14}9z^3-(700)/(423)z^5-(23,800)/(16,497)z^7

or in terms of
x,


\boxed{y(x)\approx-(x-1)-\frac{14}9(x-1)^3-(700)/(423)(x-1)^5-(23,800)/(16,497)(x-1)^7}

User JeJo
by
5.5k points